Pattern of Smoking in Medical Students - Imran Saeed Ali, Naveed Yaqoob, Ghulam Fatima, Haris Iftekhar, Mubasher Abbas (Journal of Rawalpindi Medical College, 2013)
Background: To assess the frequency and pattern of smoking in medical students. Methods: The study was conducted on a total of 975 medical students , in whom 299(30.7%) were males and rest 676(69.3%) were females. Data was collected on self administered questionnaire ensuring anonymity. The Proforma recorded age, gender, smoking or otherwise, parental and peer smoking. Results: Twenty four percent subjects smoked at least once, of which 57.7% were males and 42.3% were females. There was a higher incidence of initiation of smoking in the age groups between 16 to 20 years. Factors which influence smoking include peer smokers (41.16%) and parental(9.24%) smoking. Conclusion: Different factors which influence smoking habits need further evaluation so as to effectively control smoking.